Reaction of Algerian and international germplasm of wheat against races 1 and 5 of Pyrenophora tritici-repentis the causal agent of tan spot - Ouaar, Noureddine; Benbelkacem, Abdelkader; Singh, Pawan Kumar; Oumata, Sabrina; Benslimane, Hamida (Springer, 2022)
Tan spot caused by Pyrenophora tritici-repentis is an important foliar disease of wheat that can causes high yield losses. In Algeria, tan spot is widely present on both durum and bread wheat, the pathogen population structure was founded to be complex and showed a high molecular diversity. Among the various control measures, the most efficient and sustainable approach is the deployment of resistant cultivars. In this study, available germplasms of wheat, including 25 inbreeding lines, 54 landraces, and 37 cultivars were evaluated against races 1 and 5. Reaction of the 116 genotypes was initially evaluated under controlled conditions in seedling stage, and then the observed resistant genotypes, were evaluated in field in order to confirm their reaction against each race. Our results showed that a total 13 genotypes including inbreeding lines, landraces and cultivars showed resistant or moderately resistant reaction to race 1, while 23 genotypes, showed resistant response to race 5. However, only 1 landrace and 6 cultivars were resistant to both races 1 and 5. Genotype-resistant response in field in adult plant was similar to one recorded on growth room. These results have allowed us to recommend cultivation of some cultivars, according to races prevalent in Algerian regions, as well as recommending breeders to use the resistant sources in their breeding programs. For our knowledge, this is the first report of germplasm evaluation against tan spot disease in Algeria, and the first report of identification of resistant resources to this disease.